PERBANDINGAN UJI DIAGNOSTIK GENEXPERT MTB/RIF DENGAN KULTUR SENSITIVITAS ANTIBIOTIK DALAM MENDETEKSI RESISTENSI RIFAMPICIN Mycobacterium tuberculosis PADA PASIEN TB PARU DI RSUP H. ADAM MALIK MEDAN - Nurbaity Situmorang; Perry Boy Chandra Siahaan; Suharsih; Dewi Novina Sukapiring (Jurnal Biogenerasi, 2022)
WHO recommends GeneXpert Mycobacterium tuberculosis; Rifampicin as an initial examination for the diagnose of drug-resistant tuberculosis and drug-sensitive tuberculosis in pulmonary TB patients. The GeneXpert MTB/RIF examination is a molecular examination method with Nucleic Acid Amplification Technology (NAAT) which can diagnose TB and resistance to Rifampicin within 2 hours. The aims of this study is to determine the comparison of GeneXpert MTB/Rif Diagnostic Test with Drug Sensitivity Culture in Detecting Rifampicin M. tuberculosis resistance in TB patients at H. Adam Malik Hospital, Medan. The sample in this study was the entire population of suspected pulmonary TB at H. Adam Malik Hospital Medan who had MTB examination results. Post; rif. res. The sample size was using total sampling, namely the sampling technique where the number of samples was the same as the population, namely 128 patients in 2020. The results of the Rifampicin TCM Antibiotic Test were found that 128 people had Rifampicin Resistant results. Based on the percentage of the results of the MGIT Antibiotic Sensitivity Test, 125 people were found to have Rifampicin Resistant results and 3 people had Rifampicin Sensitive results. Based on the results, it can be seen that the sensitivity value of the TCM tool to DST MGIT culture is 97.7%. The Conclusions of these Research is the ability of the GeneXpert MTB/Rif method to detect rifampin resistance can be used as a screening tool to diagnose rifampin-resistant TB.